2002
DOI: 10.1038/sj.bjp.0704639
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐1 adrenoceptor up‐regulation induced by prazosin but not KMD‐3213 or reserpine in rats

Abstract: 1 We have investigated the e ects of chronic administration of prazosin (a subtype-nonspeci®c alpha-1 AR antagonist), KMD-3213 (an alpha-1A AR subtype-speci®c antagonist) and reserpine (a catecholamine depletor) on the density of alpha-1 AR subtypes in various rat tissues (liver, kidney, submaxillary gland, heart and spleen). H]-KMD-3213 of alpha-1 ARs in ®ve rat tissues tested. However, it caused 52% upregulation of alpha-1B AR in the spleen, and 84% and 107% up-regulation of alpha-1A-and alpha-1B ARs, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…However, in contrast with the aorta but like the tail artery, the endogenous noradrenaline level in the spleen was high and was markedly reduced by reserpine treatment. Present and previous functional or binding studies have clearly demonstrated the exclusive presence of alpha-1B AR subtype in rat spleen, irrespective of reserpine treatment (Kenakin & Novak, 1988;Yang et al, 1997;Buckner et al, 2002;Zhang et al, 2002). Thus, it does not appear that noradrenaline depletion and/or lack of adrenergic input necessarily cause the changes of alpha-1 AR expression and supersensitivity in sympathetically innervated tissues all.…”
Section: N Taki Et Al Alpha-1d Adrenoceptors In Supersensitivity 653mentioning
confidence: 66%
“…However, in contrast with the aorta but like the tail artery, the endogenous noradrenaline level in the spleen was high and was markedly reduced by reserpine treatment. Present and previous functional or binding studies have clearly demonstrated the exclusive presence of alpha-1B AR subtype in rat spleen, irrespective of reserpine treatment (Kenakin & Novak, 1988;Yang et al, 1997;Buckner et al, 2002;Zhang et al, 2002). Thus, it does not appear that noradrenaline depletion and/or lack of adrenergic input necessarily cause the changes of alpha-1 AR expression and supersensitivity in sympathetically innervated tissues all.…”
Section: N Taki Et Al Alpha-1d Adrenoceptors In Supersensitivity 653mentioning
confidence: 66%
“…The ␣ 1A, 1B -AR cell lines used in this study, which demonstrated a coexpression of these receptor populations, both exhibited ␣ 1A -AR Ͻ ␣ 1B -AR densities. This kind of subpopulation ratio has been seen in many tissues (Minneman et al, 1988;Lazou et al, 1994;Michel et al, 1994a;Zhang et al, 2002), but a distinct opposite population ratio has been observed in other tissues (Zhang et al, 2002;Tanaka et al, 2004). At first, we examined the ␣ 1A, 1B -AR cell line by a ligand binding approach and compared its properties with those of cells expressing ␣ 1A -or ␣ 1B -AR alone.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ␣ 1A -and ␣ 1B -ARs are found in different proportions to be coexpressed in brain, heart, kidney, and artery of various mammalian species (Price et al, 1994). In the rat myocardium, ␣ 1A -and ␣ 1B -ARs coexist in a 20 to 30%:70 to 80% ratio and mediate divergent effects on cardiac inotropy, rhythmicity, and cell growth (Michel et al, 1994a;Zhang et al, 2002). In rat tail artery, ␣ 1A -and ␣ 1B -ARs occur in a ratio of approximately 60%:40%, mediating adrenergic contractions (Tanaka et al, 2004).…”
mentioning
confidence: 99%
“…The difference between single and repeated dosing is most likely explained by adaptive up regulation of alpha-1 receptors in the nasal vasculature [7] ,although we did not measure nasal alpha receptor density in the present study. The same disconnect between single and chronic dosing was also seen with cardiovascular responses.…”
Section: Discussionmentioning
confidence: 87%
“…In healthy volunteers the dorsal hand vein vasoconstrictor DRC to the alpha-1 agonist phenylephrine was shifted by seven fold to the right after the first dose of the alpha-1 antagonist terazosin compared to baseline, but after 4 weeks of terazosin the dose response to phenylephrine returned back to baseline, in turn indicating that alpha-1 receptor up regulation occurs during chronic dosing [6,7].…”
Section: Introductionmentioning
confidence: 97%